2010
DOI: 10.1523/jneurosci.3066-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transfer of Visuomotor Learning between Discrete and Rhythmic Movements

Abstract: As long as we only focus on kinematics, rhythmic movement appears to be a concatenation of discrete movements or discrete movement appears to be a truncated rhythmic movement. However, whether or not the neural control processes of discrete and rhythmic movements are distinct has not yet been clearly understood. Here, we address this issue by examining the motor learning transfer between these two types of movements testing the hypothesis that distinct neural control processes should lead to distinct motor lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 31 publications
5
75
1
1
Order By: Relevance
“…In an experiment where left-hand movements, which were perturbed by a force field, were either accompanied by a nonperturbed movement of the right hand (bimanual condition) or not (unimanual condition), Nozaki and col-leagues (2006) found limited transfer of learning between these two conditions. Limited transfer of learning was also observed between rhythmic and discrete movements (Ikegami et al 2010). In addition, distinct motor plans or distinct tools are also associated with limited interference between two opposing perturbations (Cothros et al 2009;Hirashima and Nozaki 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment where left-hand movements, which were perturbed by a force field, were either accompanied by a nonperturbed movement of the right hand (bimanual condition) or not (unimanual condition), Nozaki and col-leagues (2006) found limited transfer of learning between these two conditions. Limited transfer of learning was also observed between rhythmic and discrete movements (Ikegami et al 2010). In addition, distinct motor plans or distinct tools are also associated with limited interference between two opposing perturbations (Cothros et al 2009;Hirashima and Nozaki 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the performance of motor adaptation to a visual rotation deteriorated with regard to rhythmic reaching movements, compared with a discrete reaching movement with ITIs of Ͼ1 s with respect to the rate of error reduction and converged plateau level (Ikegami et al, 2010). This implies that the impaired motor learning for rhythmic movement may be attributed to the degraded temporal association between the motor commands and the resultant movement errors.…”
Section: Introductionmentioning
confidence: 97%
“…3). Longer training with CON condition would not decrease the error to this level, because it remained unchanged by the extensive training with Ͼ1000 movement cycles (Ikegami et al, 2010). Notably, previous psychological studies (Winstein and Schmidt, 1990;Wulf and Shea, 2002) have demonstrated the beneficial effects of a reduced frequency in error feedback on motor learning.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Squares correspond to naturally occurring respiratory patterns (open, quiet breathing; filled, song); triangles correspond to inspirations following stimulation (open, quiet breathing before and after stimulations; filled, minibreath-like inspirations during and immediately after stimulation). be different, possibly paralleling differences in the generation of discrete and rhythmic movements in mammals (Ikegami et al 2010;Schaal et al 2004). Lack of stable, sustained rhythms in the song of the zebra finch may require more directive input than the driving of intrinsic rhythms emerging from the nonlinear network in the canary.…”
Section: Discussionmentioning
confidence: 99%